2023
DOI: 10.3389/fmicb.2023.1239420
|View full text |Cite
|
Sign up to set email alerts
|

Association of low HDL-c levels with severe symptoms and poor clinical prognosis in patients with severe fever and thrombocytopenia syndrome

Taihong Huang,
Yinyin Fan,
Yanyan Xia
et al.

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an acute infectious disease caused by a novel bunyavirus, characterized by high fever, thrombocytopenia, and multiple organ damage. Disturbances in lipid metabolism often occur during viral infections, but the changes and clinical significance of lipid profiles in SFTS patients remain unclear. This study aimed to investigate the alterations in lipid profiles and their clinical significance in SFTS patients.MethodsA total of 157 SFTS patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In most SFTS patients, there is a notable decrease in the platelet count, more so in severe cases. , Our findings reveal a significant negative correlation between serum ADA activity and the platelet count, indicating that ADA activity reflects disease severity. Previous studies have shown abnormal lipid metabolism in SFTS patients, with decreased HDL levels correlating with poor prognosis . HDL is known for its anti-inflammatory effects. , In our study, a negative correlation was found between ADA activity and HDL levels, suggesting a link between elevated levels of ADA and excessive inflammation in SFTS patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In most SFTS patients, there is a notable decrease in the platelet count, more so in severe cases. , Our findings reveal a significant negative correlation between serum ADA activity and the platelet count, indicating that ADA activity reflects disease severity. Previous studies have shown abnormal lipid metabolism in SFTS patients, with decreased HDL levels correlating with poor prognosis . HDL is known for its anti-inflammatory effects. , In our study, a negative correlation was found between ADA activity and HDL levels, suggesting a link between elevated levels of ADA and excessive inflammation in SFTS patients.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown abnormal lipid metabolism in SFTS patients, with decreased HDL levels correlating with poor prognosis. 26 HDL is known for its anti-inflammatory effects. 27 , 28 In our study, a negative correlation was found between ADA activity and HDL levels, suggesting a link between elevated levels of ADA and excessive inflammation in SFTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using machine learning methods, Zheng et al reported that serum cholesterol may be a relevant indicator of mortality in patients with SFTS ( Zheng et al, 2023 ). Huang et al suggested an association between low serum HDL-C levels and adverse outcomes in SFTS ( Huang et al, 2023 ). However, our findings suggest a relationship between low LDL-C levels and poor prognosis in SFTS.…”
Section: Discussionmentioning
confidence: 99%